2011
DOI: 10.1007/s10661-011-2175-7
|View full text |Cite
|
Sign up to set email alerts
|

Using watershed characteristics, sediment, and tissue of resident mollusks to identify potential sources of trace elements to streams in a complex agricultural landscape

Abstract: Trace elements used in animal feed additives can be introduced to aquatic environments through application of manures from animal feeding operations to agricultural land as fertilizer. The use of poultry feed additives containing arsenic (As) is of particular concern in the Shenandoah River watershed (Virginia, USA), an agricultural landscape with a high density of poultry operations. This study investigated the relationship between watershed characteristics of Shenandoah River tributaries and trace element co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…A majority of all pollutants, including HMs, enter water bodies with continental runoff and subsequent migration along trophic chains [1,2]. Here, some HMs are characterized by biomagnification in living organisms [3][4][5], while most HMs do not accumulate there [6,7] and ultimately are deposited in sea bottom sediments [8,9] of freshwater basins (ponds, lakes) and coastal sea areas.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of all pollutants, including HMs, enter water bodies with continental runoff and subsequent migration along trophic chains [1,2]. Here, some HMs are characterized by biomagnification in living organisms [3][4][5], while most HMs do not accumulate there [6,7] and ultimately are deposited in sea bottom sediments [8,9] of freshwater basins (ponds, lakes) and coastal sea areas.…”
Section: Introductionmentioning
confidence: 99%
“…The types of catchment land use are usually correlated with the physical and chemical parameters of the water and bottom sediments, which in turn affect the structure of lotic macroinvertebrate communities, including molluscs (Sponseller et al 2001;Erba et al 2015;Valle Junior et al 2015). For example, Ciparis et al (2012) found statistically significant relationships between catchment land use and the concentrations of heavy metals in the bottom sediments and Mollusca tissues.…”
Section: Introductionmentioning
confidence: 99%